Handling ADHD - Hand, Carol, 1945-; Dvorsky, Melissa R. (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2022)
"This book explores ADHD and how people diagnosed with the disorder manage it. It examines how ADHD affects daily life, work, and school, and it explains the latest treatments available. Features include a glossary, web resources, source notes, and an index. Aligned to Common Core Standards and correlated to state standards."--Amazon.
Includes index.
Bibliography: pages 106-109.
Keywords: Attention-deficit hyperactivity disorder; Attention-deficit hyperactivity disorder -- Diagnosis; Attention-deficit hyperactivity disorder -- Treatment